Expression profiles of neotropical termites reveal microbiota-associated, caste-biased genes and biotechnological targets - Campanini, E. B.; Pedrino, M.; Martins, L. A.; Athaide Neta, O. S.; Carazzolle, M. F.; Ciancaglini, I.; Malavazi, I.; Costa-Leonardo, A. M. [UNESP]; de Melo Freire, C. C.; Nunes, F. M.F.; da Cunha, A. F. (Wiley, 2021)
Termites are well recognized by their complex development trajectories, involving dynamic differentiation process between non-reproductive castes, workers and soldiers. These insects are associated with endosymbiotic microorganisms, which help in lignocellulose digestion and nitrogen metabolism. Aiming to identify genes harbouring biotechnological potential, we analyzed workers and soldiers RNA-Seq data of three neotropical termites: Heterotermes tenuis (Isoptera: Rhinotermitidae), Velocitermes heteropterus (Isoptera: Termitidae) and Cornitermes cumulans (Isoptera: Termitidae). We observed differences in the microbiota associated with each termite family, and found protists' genes in both Termitidae species. We found an opposite pattern of caste-biased gene expression between H. tenuis and the termitids studied. Moreover, the two termitids are considerably different concerning the number of differentially expressed genes (DEGs). Functional annotation indicated considerable differences in caste-biased gene content between V. heteropterus and C. cumulans, even though they share similar diet and biological niche. Among the most DEGs, we highlighted those involved in caste differentiation and cellulose digestion, which are attractive targets for studying more efficient technologies for termite control, biomass digestion and other biotechnological applications.
Keywords: cellulolytic genes; meta-transcriptomes; Rhinotermitidae; Termitidae